Prevalence and associated factors of stress in the Malaysian Police Force - Retneswari, M.; Bulgiba, A.; Chinna, K.; Darus, A.; Isahak, M.; Shathanapriya, K.; Koh, D. (2013)
Objective: This study aims to determine the prevalence of stress and the associated socio-demographic and work factors among police personnel in Metropolitan Kuala Lumpur, Malaysia. Method: A cross-sectional study was conducted in two randomly selected police districts in Kuala Lumpur from 2009 to 2011. A total of 579 police officers from 11 police stations and two headquarters participated in this study. The 21-item Depression, Anxiety and Stress questionnaire was used. Multinomial logistic regression analyses were carried out to examine the effect of socio-demographic and work factors on stress. Results: The overall prevalence of stress was 38.8 (95 CI 34.2, 43.6) with 5.9 (3.9, 8.8), 14.9 (11.6, 18.8) and 18.0 (14.5, 22.2) for severe, moderate and mild stress, respectively. Inspectors were more likely to suffer from severe stress (aOR 10.68, 95 CI 3.51, 32.53) compared to junior officers. Those who complained that their salaries were not commensurate with their jobs were more likely to suffer from moderate levels of stress (aOR 2.73, 95 CI 1.43, 5.22) compared to those who were happy with their salaries. Conclusions: This study strengthens findings that police job is stressful. Special attention needs to be paid to Inspector-level ranks and the remuneration structure of police officers to address this issue.